1996
DOI: 10.1073/pnas.93.4.1716
|View full text |Cite
|
Sign up to set email alerts
|

The treatment of chronic progressive multiple sclerosis with cladribine.

Abstract: A 2-year, placebo-controlled, double-blind, crossover study was started in 1992 to evaluate cladribine, an immunosuppressive drug, in the treatment of chronic progressive multiple sclerosis. In the first year patients were given cladribine 0.10 mg/kg per day for 7 days as four monthly courses for a total of 2.8 mg/kg or placebo. During the second year patients treated with placebo during the first year were given i.v. infusions of 0.10 mg, 0.05 mg, and 0. Since there is no satisfactory treatment for chronic pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
136
1
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(144 citation statements)
references
References 21 publications
6
136
1
1
Order By: Relevance
“…In support of this decision we considered the evidence for Cladribine being effective in pwMS from previous phase III trials,10, 11 and our recent work demonstrating there is no short‐term increase in the risk of cancer with Cladribine compared to licensed DMT 12. Moreover, earlier phase II trials providing evidence of efficacy in pwPMS13, 14, 15 the convenience of an induction treatment, and the availability of Cladribine as an off‐label drug for people with hairy cell leukemia all played a role in this decision. Finally, Cladribine penetrates into the CNS,16 which may be advantageous in pwPMS through treatment effect on meningeal B and T lymphocyte clusters described in post mortem samples of pwPMS 17…”
Section: Discussionmentioning
confidence: 99%
“…In support of this decision we considered the evidence for Cladribine being effective in pwMS from previous phase III trials,10, 11 and our recent work demonstrating there is no short‐term increase in the risk of cancer with Cladribine compared to licensed DMT 12. Moreover, earlier phase II trials providing evidence of efficacy in pwPMS13, 14, 15 the convenience of an induction treatment, and the availability of Cladribine as an off‐label drug for people with hairy cell leukemia all played a role in this decision. Finally, Cladribine penetrates into the CNS,16 which may be advantageous in pwPMS through treatment effect on meningeal B and T lymphocyte clusters described in post mortem samples of pwPMS 17…”
Section: Discussionmentioning
confidence: 99%
“…Smaller placebo-controlled trials of subcutaneously administered cladribine in chronic progressive and relapsing-remitting MS revealed promising results, not only clinically but also in MRI parameters. [72][73][74] However, a double-blind, placebo-controlled phase III study of subcutaneously administered cladribine in 159 patients with secondary and primary progressive MS unexpectedly failed to exhibit significant clinical and MRI benefits after one year. 75 As cladribine also exists in an oral formulation and as pilot trials also have provided encouraging data, 76 a large randomized, double-blind, placebocontrolled phase III trial, including 1,290 patients with active inflammatory relapsing-remitting MS has recently been initiated.…”
Section: Cladribinementioning
confidence: 99%
“…[23][24][25] In the placebo-controlled phases of these studies, 183 patients received intravenous or subcutaneous cladribine, at doses of 0.7-2.8 mg/kg, administered in monthly 5-to 7-day courses for 2-6 months, and were followed for up to 24 months. These studies showed statistically-significant improvement in MRI measures of activity (Table 1).…”
Section: Clinical Efficacy and Safety Profile Of Cladribine In Ms CLImentioning
confidence: 99%
“…Cladribine is able to cross the blood-brain barrier (BBB) 22 and is, therefore, likely to act on cells in both the periphery and CNS appearing to have a greater effect on CD4+ T cells than the CD8+ T cell population. 23 The parenteral formulation of cladribine has been used extensively for the reduction of aberrant lymphocyte populations in the hematological oncology setting. It is indicated for the treatment of hairy cell leukemia (HCL), and has been used in the treatment of several other leukemias and lymphomas.…”
mentioning
confidence: 99%
See 1 more Smart Citation